Čiara = The line [videorecording (DVD)] - Bebjak, Peter; Maštalír, Tomáš, 1977-; Boklan, Stanislav, 1960-; Fialová, Zuzana, 1974-; Geza, Benko; Hryc, Andrej, 1949-2021; Kaňkovský, Filip, 1985-; Vášáryová, Emília, 1942-; Balko, Peter, 1988- (Synergetic Distribution, 2025)
A hectic time begins for Adam Krajnak, the father of a family and the head of organized crime on Slovakian-Ukrainian borderlands - his oldest daughter is about to marry a local thief named Ivor, Adam's Ukrainian partner Iona begins to rebel, and a new product - narcotics begin to appear on the border. Directed by Slovakian director Peter Bebjak. Winner of 9 awards, and 10 nominations.